Isolation, Purification and Identification of Xanthomonas oryzae pv. oryzae - Srinivas, Bhukya; Patil, V. A.; Venu, Emmadi; Hariprasath, M.; Purushotham, Pooja; Rajeswari, Emani; Vasanth, Yerram; Srinivas, Katravath; Aravind, K.; Kumar, Eadulla Praveen; Rajesh, K. (International Journal of Economic Plants, 2024)
The present study was conducted during kharif (July-November, 2020) at the Department of plant pathology, N. M. College of Agriculture, Navsari Agricultural University, Navsari, Gujarat, India to isolate, purify and identify the pathogen responsible for rice bacterial blight. The pathogen was isolated from infected rice leaves and purified through streaking techniques, with its cultural and morphological characteristics utilized for identification. The analysis revealed that colonies grown on nutrient agar media exhibited traits consistent with Xanthomonas oryzae pv. oryzae, appearing raised, creamy yellow, smooth, entire and buttery as cultural characteristics and the bacterium as possessing a rod-shaped structure, gram-negative staining, encapsulation and non-spore formation as morphological characteristics. Furthermore, a pathogenicity test was conducted on the susceptible rice cultivar GR-11, cultivated in pots under controlled conditions within a net house was successfully satisfying Koch’s postulates. Rice (Oryza sativa L.) is one of the important cereal crop and a crucial dietary staple grown extensively in Gujarat, where it plays a significant role in ensuring food security and sustainability. However, rice bacterial blight remains a persistent threat, leading to substantial losses in both quantity and quality. To address this issue the investigation provided valuable insights into understanding the pathogen, thereby contributing to the development of cost-effective solutions for managing rice bacterial blight, which helps in increasing crop yield to the rice growing farmers of Gujarat.